Bimbingan Konseling Pada Anak Usia Dini - Annisa Zakia Nasution; Juraidah Br. Sembiring; Rafiqah Hayati; Fauziah Nasution (Al Tahdzib: Jurnal Pendidikan Islam Anak Usia Dini, 2023)
Guidance and counseling for early childhood is an assistance effort carried out by teachers/supporters for early childhood so that children can grow and develop optimally and be able to overcome the problems they face. The research was carried out in a qualitative manner using a literature study approach. Research results: Through counseling, children are taught skills that enable them to become independent individuals, able to make decisions, and be responsible for their own actions. The main objective of providing guidance and counseling is to anticipate or take preventive action against the emergence of problematic behavior. Of course, prevention will be much easier than cure. This principle will also be applied in counseling guidance in the Early Childhood Education environment. In other words, preventing problem behavior in children is much easier than treating problem behavior in adults.